The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1534/genetics.118.301305
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Screen Reveals a Role for the HIR Histone Chaperone Complex in Preventing Mislocalization of Budding Yeast CENP-A

Abstract: Centromeric localization of the evolutionarily conserved centromere-specific histone H3 variant CENP-A (Cse4 in yeast) is essential for faithful chromosome segregation. Overexpression and mislocalization of CENP-A lead to chromosome segregation defects in yeast, flies, and human cells. Overexpression of CENP-A has been observed in human cancers; however, the molecular mechanisms preventing CENP-A mislocalization are not fully understood. Here, we used a genome-wide synthetic genetic array (SGA) to identify gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 85 publications
2
27
0
Order By: Relevance
“…We investigated the physiological consequences of defects in Cse4 proteolysis in met30-6 and cdc4-1 strains. Increased stability of overexpressed Cse4 in psh1Δ, slx5Δ and hir2Δ strains correlates with its mislocalization to non-centromeric regions [24][25][26]33]. We reasoned that the strong defects in proteolysis of endogenous Cse4 may contribute to its mislocalization and CIN in met30-6 and cdc4-1 strains.…”
Section: Scf-met30 and Scf-cdc4 Prevent Mislocalization Of Cse4 To Nomentioning
confidence: 99%
See 4 more Smart Citations
“…We investigated the physiological consequences of defects in Cse4 proteolysis in met30-6 and cdc4-1 strains. Increased stability of overexpressed Cse4 in psh1Δ, slx5Δ and hir2Δ strains correlates with its mislocalization to non-centromeric regions [24][25][26]33]. We reasoned that the strong defects in proteolysis of endogenous Cse4 may contribute to its mislocalization and CIN in met30-6 and cdc4-1 strains.…”
Section: Scf-met30 and Scf-cdc4 Prevent Mislocalization Of Cse4 To Nomentioning
confidence: 99%
“…The rationale for this is based on the essential role of the N-terminus for its interactions with kinetochore proteins, Ub-mediated proteolysis and post-translational modifications (PTMs) of Cse4 [19,26,27,[54][55][56][57][58][59][60][61][62]. Furthermore, we recently showed that hir mutants, which are defective in proteolysis of overexpressed Cse4, are sensitive to GAL-CSE4 but not GAL-cse4Δ129 (Cse4 lacking the N-terminal domain) [33]. Growth assays showed that GAL-cse4Δ129 did not result in lethality in WT, met30-6 or cdc4-1 strains (Fig 2A), suggesting that the N-terminus of Cse4 is required for the SDL of GAL-CSE4.…”
Section: Mutants Of Scf-met30 and Scf-cdc4 Exhibit Sdl With Overexprementioning
confidence: 99%
See 3 more Smart Citations